A flexible modelling approach for capturing plastic anisotropy and strength differential effects exhibited by commercially pure titanium. (15th October 2018) - Manopulo, Niko; Raemy, Christian; Hora, Pavel
Abstract: Commercially pure titanium exhibits strong anisotropy, strength differential as well as texture evolution, which make the development of predictive simulation models a challenging task. A new modeling approach is proposed based on the homogeneous distortion of well-established yield surface descriptions, in order to achieve a flexible tool to capture all the mentioned effects. The models are calibrated based on uniaxial tensile and compression tests and are validated based on the earing profile and thickness distribution of cup drawing experiments.